Characteristic of Physical and Chemical in Randusanga Kulon Waters, Brebes for Suitability of Green Mussel (Perna viridis) Cultivation - Nisa, Mufidah Rohmatun; Amalia, Hasnita Puspa; Paramitha, Laura Keisya; Sanjayasari, Dyahruri (Jurnal Sains dan Teknologi Perikanan, 2025)
Randusanga Kulon waters as a habitat of green mussels had potential as a cultivation area. The prospect of the economy of green mussels cultivation is high due to rapid growth, available annually, and can tolerate the environmental changes. This study was aimed to identify the water quality in Randusanga Kulon waters for green mussel cultivation, there are physical and chemical characteristics such as temperature, turbidity, water clarity, TSS, TDS, and salinity, pH, DO, ammonia. The sampling was conducted on December 2024 using purposive sampling method by setting up 3 stations based on distance, the results are compared with quality standard of PP No. 22 2021. The result of physical characteristic, average temperature at three station is 31°C, turbidity range between 4-27 NTU, water clarity range between 15-50 cm, TSS range between 72-93 mg/L, TDS range between 204-304 mg/L. The results of chemical characteristic, average salinity at three station is 25 ‰, average pH is 7, DO range between 4-5 mg/L, ammonia range between 0.092-0.199 mg/L. The results showed some of parameters were exceed the quality standard of PP No. 22 2021 therefore the conditions of Randusanga Kulon waters still suitability for green mussel cultivation.